Uma proposta de sequência didática para o ensino de radiação solar: Entendimentos e proposições - Mendes, Amanda Cristina (2023)
Brazilian education has been going through several moments of reformulation of guiding documents. In the case of the National Education Guidelines and Bases Law (LDB, 1996), the National Education Plan (PNE, 2014), the National Curricular Guidelines for Basic Education (DCN, 2013). At present, even though the majority of students, theoretically, are at the appropriate age for their respective school year and that, according to the PNAD (2016), the gross school attendance rate of people aged 6 to 14 has reached 98.6%, the school grade-age gap still remains an obstacle to be faced. Students who, at the beginning of each school year, do not have years of study compatible with their age are considered to be behind in school. One of the consequences of the age-grade gap is the low performance of students who are behind in school compared to regular students. Based on the above, this work seeks to understand the gap in school learning, especially that related to the teaching of Natural Sciences in Basic Education. To this end, we use the possibilities of addressing this gap with the development of a Didactic Sequence (SD), with input from Digital Information and Communication Technologies (DIT). The didactic sequence was developed with support from the Three Pedagogical Moments (TMP), on the topic “Solar radiation and implications for human life”, given the interdisciplinary relationships of this content with the other subjects of the basic curriculum, the diversity of information related to this radiation and the development of activities based on real everyday situations. It was possible to observe, during the development of this SD, that the students developed scientific concepts, under the dynamics of the TMP, and taking into account the spontaneous conceptions related to the phenomena observed in the context of the activities carried out, providing them with greater protagonist and autonomy. The interdisciplinary approach, together with the use of TDIC in school practice, to solve problems and disseminate information, gave students the opportunity to correlate their knowledge on certain subjects and content with the difficulties they faced and the learning skills they possessed. It is clear that the skills achieved in each stage of DS allowed the achievement of learning surrounded by meaning. From this perspective, the educational product created/developed, or part of it, therefore serves as support and suggestion for classes that are based on interdisciplinarity between Natural Sciences disciplines with input from Digital Information and Communication Technologies (TDIC).